Community perception on service quality at an international higher education institution: a case study - Ibrahim, Haslina; Abdul Rahim, Adibah; Abdul Rahman, Amilah; Abdullah, Nur Anisah (2012)
This paper reports on the exploration on community perception of higher education institution service quality from three dimensions namely academic, administrative and facilities. Focus group discussions were used for data collection involving three groups of neighbouring communities from both urban and rural areas. The objectives include to better understand issues and concerns facing the community; and in doing so highlight the aspects of services needing urgent attention. Thus, findings from the research exercise are grounded on empirical evidences promoting and recognizing community engagement and inclusiveness. It is hoped that by developing such mutual relationships the Institution could respond to the real community needs and expectations in delivering useful services as an effort to retain its relevance to the society. The findings from this study could inform the enhancement of management practice at the Institution. In this respect, there would be community engagement in taking the university forward as well as imparting the university’s role in transforming the lives of the community. While this study was useful in bringing some service quality issues to light, but it was only for a particular period. The Institution ought to continuously engage its stakeholders in dialogues on how things could be better as an effort to deliver seamless and painless services. Keyword: academic service quality; administrative service quality; facilities service quality; international higher education institution; community engagement.